A Large Database Evaluation of Infection and Nonunion Following Ankle Arthrodesis: Does Pain Regimen Matter?. Issue 4 (November 2022) - Sokil, Laura E.; Wong, Liam H.; Chrea, Bopha; Meeker, James E.; Yoo, Jung; Atwater, Lara C.
Category: Ankle Arthritis; Ankle Introduction/Purpose: Multimodal therapies are critical for limiting use of opioids for postoperative pain control after orthopaedic procedures. Though NSAIDs and COX-2 inhibitors are effective non-opioid adjuncts for postoperative pain, animal models have demonstrated increased rates of nonunion or delayed union in the presence of NSAIDs. Nonunion or delayed union results in a protracted postoperative course that may warrant longer duration of surveillance or revision procedures. Retrospective studies and meta-analyses investigating NSAID use and bone healing have conflicting findings. Additionally, there are few studies investigating NSAID use and other adverse events such as postoperative infection. Improved understanding of the impact of NSAID use on union rates and infection after ankle arthrodesis will allow practitioners to optimize safe, effective pain control while limiting risk of nonunion. Methods: This large retrospective database study queried a national insurance claims database (PearlDiver Technologies) for patients undergoing ankle arthrodesis from 2015 through 2019 as identified by ICD-10 codes. Patients prescribed NSAIDs or COX-2 inhibitors within six weeks following ankle arthrodesis were identified. Patients with any operation one year prior to or following ankle arthrodesis were excluded from analysis to prevent attributing complications to another operation. Association between NSAID or COX-2 inhibitor use and infection or nonunion following ankle arthrodesis were analyzed using multivariable logistic regression analyses. To adjust for comorbid conditions, multivariable models included age at time of operation, sex, obesity, tobacco use, and diabetes. Results: Our query yielded 2, 355 patients in the five-year period who underwent ankle arthrodesis. 257 (11%) patients were prescribed NSAIDs following surgery and 56 (2.4%) patients were prescribed COX-2 inhibitors. Infection risk was similar between patients not prescribed either medication (n=92, 4.5%) and those treated with NSAIDs (n=14, 5.4%; P=0.60) or COX-2 inhibitors (n=2, 3.5%; P=0.99). The nonunion rate between patients not prescribed either medication (n=232, 11%) was similar to those treated with COX-2 inhibitors (n=8, 14%; P=0.64), but increased in patients treated with NSAIDs (n=45, 18%; P=0.006). On multivariable analysis, tobacco use (OR, 1.46; 95% CI, 1.09-1.94), obesity (OR, 2.08; 95% CI, 1.57-2.76), and NSAID use (OR, 1.53; 95% CI, 1.06-2.17) were associated with increased odds of nonunion after ankle arthrodesis (all P<0.02) (Table). Conclusion: Analysis of the PearlDiver database, the largest available administrative claims database, for 2, 355 patients undergoing ankle arthrodesis demonstrated an 11% risk of nonunion and 4.5% risk of infection. The risk of nonunion is increased in patients prescribed NSAIDs within six weeks postoperatively (18%). After adjusting for comorbid conditions associated with nonunion, such as tobacco use and obesity, NSAID use increased risk of nonunion whereas COX-2 inhibitor use did not. Prospective investigation is necessary to better understand these relationships, however, our analysis suggests practitioners should judiciously utilize NSAIDs and consider use of COX-2 inhibitors for pain control after ankle arthrodesis surgery.